"Life Savers": Technology and White Masculinities in Twitter-Based Superhero Film Promotion. (June 2018) - Cummings, Kelsey
Drawing from social media studies and the literature on American economic decline and conceptualizations of gender and sexuality, this article asks how Twitter's medium-specific features can be understood through an examination of its representational qualities in the context of the promotion of two contemporary superhero films. The accounts @BatmanvSuperman and @SpiderManMovie provide case studies of film promotion that uses Twitter's particularities as a platform in order to advance distinct narratives about the films being promoted, via original tweets and retweets that, respectively, represent differing approaches to advertisement. Through this study, the article advances the arguments, first, that cultural representations are reflective of Twitter's specificities as a social media platform, and second, that these representations work in conjunction with cultural norms of the contemporary US. One form of idealized White masculinity advanced by the latter is reliant on technology and its merging with the White man's body. As a result, the technologies of superheroes' suits as well as Twitter itself become representative of the present sociopolitical climate and its various aspirations and anxieties.